2019
DOI: 10.14814/phy2.14141
|View full text |Cite
|
Sign up to set email alerts
|

Metformin modulates immune cell infiltration into the kidney during unilateral ureteral obstruction in mice

Abstract: Metformin is today the first choice treatment for type‐2 diabetes, but has also protective effects in several renal disease models. Previously, we have demonstrated that the protective effects in response to unilateral ureteral obstruction ( UUO ) are independent of organic cation transporters ( OCT s), the transporters responsible for the metformin uptake into the renal cells. The mechanisms behind the renoprotective effects are incompletely understood, but our pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
3
10
1
1
Order By: Relevance
“…The anti-oncogene effects of metformin have been suggested to involve inhibition of the STAT3 pathway, which can also prevent monocyte-to-macrophage differentiation [16,22]. We previously postulated that metformin attenuated immune cell infiltration by reducing pSTAT3 expression [14]. However, we did not observe any immunoregulatory effects of phenformin, despite a significant impact on pSTAT3 levels.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…The anti-oncogene effects of metformin have been suggested to involve inhibition of the STAT3 pathway, which can also prevent monocyte-to-macrophage differentiation [16,22]. We previously postulated that metformin attenuated immune cell infiltration by reducing pSTAT3 expression [14]. However, we did not observe any immunoregulatory effects of phenformin, despite a significant impact on pSTAT3 levels.…”
Section: Discussioncontrasting
confidence: 80%
“…We have recently shown that metformin decreases the expression of VCAM and ICAM and limits immune cell infiltration into UUO kidneys [6]. In addition, metformin modulates immune cell composition on a systemic level, indicating whole-body mechanisms underlying the renoprotective effects of metformin [14]. However, our current data indicate that the renoprotective effects of phenformin are independent of immunoregulatory effects.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…They observed that metformin attenuates these inductions by UUO in AMPK-β1-deficient mice, suggesting that the renoprotective effects of metformin are independent of OCT1/2 and AMPK [ 72 ]. Accordingly, they reported that metformin inhibits STAT3-mediated immune cell infiltration, tubular damage and fibrosis in a UUO mice model, which may explain the AMPK-independent mechanisms [ 73 ]. Feng et al showed that metformin attenuates UUO-induced renal fibrosis in AMPKα2-deficient mice [ 74 ].…”
Section: Basic Mechanisms Underlying the Effects Of Metformin On Dmentioning
confidence: 99%